(untitled) - Urban, Mychael (Hoboken, N.J., 2005)
Aces is a fascinating look at three of the best pitchers in the game. I learned a lot about Hudson, Mulder and Zito that I wish I'd known before. Mychael Urban proves again that it takes a pitcher to know a pitcher
Keywords: Pitchers (Baseball),Môn bóng chày; United States,Nước Mỹ